Effects of aromatherapy and massage on pain of patients with multiple sclerosis - Atashzadeh Shorideh, F; Mohammadi, Sh; Abed Saeedi, Zh; Alavi Majd, H; Salehi Sormeghi, M (Advances in Nursing & Midwifery, 2009)
Background Multiple sclerosis (MS) is one of common autoimmune diseases with 0.1% incidence in the world population. Pain is one of its clinical manifestations and, according to recent studies, it mostly remains untreated. Pain relief is a primary nursing intervention and, currently, complementary therapies such as massage and aromatherapy are increasingly used for it. Purpose This quasi-experimental study was conducted to compare between the effects of massage with menthol (aromatherapy) and sweet almond on MS-related pain in patients referring to Mazandaran MS Association in Sari, 2006. Methods 80 MS patients were selected by purposive sampling method. Inclusion criteria consisted of age between 20 and 40; no massage prohibition; presence of pain in lumbar or distal extremities; no history of allergy, headache and respiratory diseases. Data were collected by a questionnaire in two parts: demographics and McGill pain scale (0-5). Its validity and reliability were checked by content and internal consistency (r=0.88) methods respectively. Patients were randomly divided into two groups: massage group receiving sweet almond massage and aromatherapy group receiving aromatic (mint abstract) menthol massage. Severity of pain was recorded and compared before and after the intervention. Results Finding showed no difference between the groups in terms of demographic data and pain severity before the intervention (P< 0.05). On the other hand, a significant difference was found within (P<0.001) and between (P<0.001) the groups after the intervention. Conclusion It can be concluded that both methods have significant effects on pain severity but massage with menthol is more effective. Since studies in this regard are limited, further investigations are warranted. Keywords Multiple sclerosis, Pain, Massage, Aromatherapy, Menthol, Mint abstract Background Multiple sclerosis (MS) is one of common autoimmune diseases with 0.1% incidence in the world population. Pain is one of its clinical manifestations and, according to recent studies, it mostly remains untreated. Pain relief is a primary nursing intervention and, currently, complementary therapies such as massage and aromatherapy are increasingly used for it. Purpose This quasi-experimental study was conducted to compare between the effects of massage with menthol (aromatherapy) and sweet almond on MS-related pain in patients referring to Mazandaran MS Association in Sari, 2006. Methods 80 MS patients were selected by purposive sampling method. Inclusion criteria consisted of age between 20 and 40; no massage prohibition; presence of pain in lumbar or distal extremities; no history of allergy, headache and respiratory diseases. Data were collected by a questionnaire in two parts: demographics and McGill pain scale (0-5). Its validity and reliability were checked by content and internal consistency (r=0.88) methods respectively. Patients were randomly divided into two groups: massage group receiving sweet almond massage and aromatherapy group receiving aromatic (mint abstract) menthol massage. Severity of pain was recorded and compared before and after the intervention. Results Finding showed no difference between the groups in terms of demographic data and pain severity before the intervention (P< 0.05). On the other hand, a significant difference was found within (P<0.001) and between (P<0.001) the groups after the intervention. Conclusion It can be concluded that both methods have significant effects on pain severity but massage with menthol is more effective. Since studies in this regard are limited, further investigations are warranted. Keywords Multiple sclerosis, Pain, Massage, Aromatherapy, Menthol, Mint abstract